Proverbs: Prose or poetry? - Viljoen, Anneke (HTS teologiese studies, 2015)
Should Proverbs be read as prose or poetry? Considering the language craft is of essential significance for a hermeneutical enquiry into the biblical book of Proverbs. Five suppositions to support the presupposition that Proverbs is best read as poetry were considered.